2012
DOI: 10.1209/0295-5075/99/48008
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of DNA on a supported lipid membrane

Abstract: We utilize real-time single-molecule imaging to investigate the transient response of DNA molecules on a rigidly supported lipid membrane upon their adsorptions. Following the stochastic landing onto the membrane at a nearly spherical initial state, these DNA coils gradually relax and expand their apparent size (R 2 g,xy ) in a highly anisotropic fashion. The evolution of R 2 g,xy exhibits considerable variations among individual molecules, and its time dependence can be characterized by a generic exponential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…We have calculated the in‐plane mean square radius of gyration < R Gǁ 2 > and the in‐plane asphericity parameter < A ǁ > for the polymer chains in the repulsive slit. < A ǁ > represents the 2D instantaneous shape of the polymer chain parallel to the surface, which is defined as A||=(L12L22)2(L12+L22)2, in which L12 and L22 are two eigenvalues of a 2D gyration tensor: Sxy=1Ni=1NsisiT=true(SxxSxySxySyytrue), where si=col(xi,yi) is the position vector of the monomer i in the frame of reference with its origin at the center of mass of the whole polymer chain, and s i T is the transposed matrix of s i . A ǁ varies from 0 for 2D circular shape to 1 for long rod.…”
Section: Resultsmentioning
confidence: 99%
“…We have calculated the in‐plane mean square radius of gyration < R Gǁ 2 > and the in‐plane asphericity parameter < A ǁ > for the polymer chains in the repulsive slit. < A ǁ > represents the 2D instantaneous shape of the polymer chain parallel to the surface, which is defined as A||=(L12L22)2(L12+L22)2, in which L12 and L22 are two eigenvalues of a 2D gyration tensor: Sxy=1Ni=1NsisiT=true(SxxSxySxySyytrue), where si=col(xi,yi) is the position vector of the monomer i in the frame of reference with its origin at the center of mass of the whole polymer chain, and s i T is the transposed matrix of s i . A ǁ varies from 0 for 2D circular shape to 1 for long rod.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the adsorption of polymers also relates to DNA packaging in viruses, and immobilization of enzyme . The adsorption of polymers on solid surface or membrane is an important research topic and has attracted extensive attention from experiments, theory, and computation simulations . Experiments and simulation studies on polymer adsorption showed that polymers would change their size and shape after adsorption …”
Section: Introductionmentioning
confidence: 99%
“…The adsorption transitions were well studied for both collapsed and extended conformations . Polymer conformation is changed during the adsorption . For both collapsed and extended conformations, the statistical size parallel to the surface is increased obviously at E PS > EPSCAP .…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of flexible polymers can significantly and permanently modify the properties of surfaces1. Simultaneously the attractive surface also changes the conformational and dynamic properties of polymers234. The properties of adsorbed polymers play important roles in many chemical and biological applications1567, such as polymer nanocomposite materials8, compatibilization by copolymers91011, colloid stabilization by polymeric surfactants1213, coating and lubrication14, and DNA segregating in bacteria15 and packaging in viruses16.…”
mentioning
confidence: 99%
“…The properties of adsorbed polymers play important roles in many chemical and biological applications1567, such as polymer nanocomposite materials8, compatibilization by copolymers91011, colloid stabilization by polymeric surfactants1213, coating and lubrication14, and DNA segregating in bacteria15 and packaging in viruses16. The adsorption of polymers on surfaces/interfaces and the dynamical properties of adsorbed polymers have motivated extensive studies in experiment3171819202122232425, theory and simulation24262728293031323334353637383940414243444546474849.…”
mentioning
confidence: 99%